Preliminary study of velocity-space distribution of fast-ion loss under ion cyclotron resonance heating in the EAST - WANG Shusong; HUANG Juan; CHANG Jiafeng; ZHANG Xinjun; GAO Wei; FU Jing; SUN Yanxu; SHI Chang; WANG Xihui; ZHANG Zixin (He jishu, 2023)
BackgroundScintillator-based fast-ion loss detector (FILD) can measure the velocity-space distribution of fast-ion loss and are key in studying the control mechanism of fast-ion loss in nuclear fusion devices.PurposeThis study aims to obtain the velocity-space distribution of fast-ion loss from corresponding FILD data and evaluate the capacity of current FILD probe for the further improvement of diagnostic design.MethodsThe FILDSIM code was employed to establish the linkage between the fast-ion image digitized by FILD and the velocity-space distribution of fast-ion loss. The detection coverage of fast ions on the scintillator was assessed through reverse tracing of the lost fast ions, considering the geometry of the FILD probe as well as the pitch angle and gyroradius of fast ions entering the pinhole of the FILD probe.ResultsThe obtained velocity-space distribution of fast-ion loss under ICRH indicates that the energy of lost fast hydrogen minority ions is above 200 keV. Moreover, analysis shows that the geometry of the probe, particularly the shell behind the scintillator, obstructs the diagnostic detection range, creating a null region on the scintillator.ConclusionsThe acquisition of the velocity-space distribution of fast-ion loss lays the foundation for further evaluation and control of fast-ion loss under ion cyclotron resonance heating. In addition, the investigation of the probe detection range provides a basis for upgrading diagnostic systems.